How online advertising competes with user-generated content in TripAdvisor. A neuroscientific approach - Bigne, Enrique; Simonetti, Aline; Ruiz, Carla; Kakaria, Shobhit (Journal of business research, 2021)
•Advertising content embedded in social media positively affects visual attention.•Advertising content embedded on social media does not affect consumer engagement.•UGC valence-ad congruence has no interaction effect on ad recall.•Ad congruence impacts on ad recall and visual attention.•Congruent ad-media contexts are peripheral cues in message processing. Drawing on cognitive load theory, congruence research, and dual processing models, the purpose of this study is to determine the effectiveness of online advertising in social media. To this end, three separate studies were conducted. First, using eye-tracking and electroencephalography, we examine the differences, based on whether or not an ad is embedded, in subjects’ visual attention and engagement in a TripAdvisor webpage. Our findings showed that synergies between social media content and advertising content positively affect users’ visual attention. A second study, using an online survey, assessed the impact of congruent/incongruent ads on ad recall. A third study, using eye-tracking, assessed the impact of congruent/incongruent ads on visual attention. Our findings suggest that consumers exposed to online ads for very limited time periods rely on less effortful, more heuristic, context-based processing strategies. Congruent ad-media contexts can act as peripheral cues, activating knowledge structures and facilitating message processing.